KOMPOSISI ASAM LEMAK CACING LAUT SIASIA (SIPUNCULUS, SP) DARI PERAIRAN PANTAI PULAU NUSALAUT - Bernita Silaban (BIOPENDIX, 2017)
Background: "Siasia" is a seaworm species in the phylum that includes Sipuncula Sipunculidea class. This animal has been consumed for generations by coastal communities Nusalaut Island, central mollucas but not yet universally known. Until now there has been obtained gisi complete composition. This study aimed to identify the composition of fatty acids contained in vain fresh seaworms. Methods: Seaworms vain taken from coastal waters of Negeri Titawaai and Nalahia Nusalaut Island, Central Moluccas in March 2014. The parameters analyzed include methods is sokhlet fat content and fatty acid by GC method. Results: The results showed fresh siasia fat content 1.12% of coastal waters Titawaai while 1.91% of coastal waters Nalahia. Fatty acids seaworms were identified from coastal waters Titawai is kaparat acid (C10: 0), lauric acid (C12: 0), myristic acid (C14: 0), palmitoleic acid (C16: 1), stearic acid (C18: 0), linolenic acid (C18: 3) acid and eicosapentaenoic (C20: 5) while the fatty acids of seaworm vain of coastal waters Nalahia include is lauric acid (C12: 0), myristic acid (C14: 0), palmitoleic acid ( C16: 1), stearic acid (C18: 0) and eicosapentaenoic acid (C20: 3). Conclusion: The fat content of fresh siasia sea worms is 1.12% from the waters of Titawaai beach, while 1.91% of the waters of the coast of Nalahia.